Pengembangan Sistem Pendidikan Pondok Modern Dalam Meningkatkan Profesionalisme Santri - Rusydi, Muhammad; Alfatani, Ifan Ali (Universitas KH. A. Wahab Hasbullah, 2023)
The results of the research carried out by the author can be conveyed here that the strategy for developing the education system carried out by PM Al-Rifa'ie in increasing the professionalism of students is: through an educational program consisting of formal education and religious education, an orderly organizational system in the modern Al-Rifa'ie Islamic boarding school. Rifa'ie, employee recruitment, curriculum development program. Meanwhile, the constraining factors are teaching staff factors, student/student factors, student/student guardian factors, organizational factors, and environmental factors. And the efforts made by PM Al-Rifa'ie to increase the professionalism of students are: providing educational facilities and other facilities that provide adequate support, providing life skills provision through extracurricular activities, holding training and training or seminars for all teachers, both formal teachers and teachers. diniyah and murottil Qur'an teachers, and training, training and seminars for students.